2017
DOI: 10.4103/2303-9027.204812
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solid pancreatic mass lesions on pancreatic duct diameter at endoscopic ultrasound

Abstract: Objectives:To evaluate the effect of solid pancreatic masses on the pancreatic duct (PD) at the endoscopic ultrasound (EUS) and the relationship of the location/size of a mass and PD dilation.Materials and Methods:Patients who underwent EUS for pancreatic indications from 2011 to 2013 at a single center were retrospectively identified. Those with biopsies that revealed adenocarcinoma or neuroendocrine tumors in the pancreas were identified and PD size was ascertained from EUS, computed tomography, or magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…The ROC curves of different ultrasomics models based on eight machine-learning algorithms for predicting PNET. volume of PNET was notably smaller than that of pancreatic adenocarcinomas (25). In summary, the characteristics of the clinical and EUS ultrasonic features observed in this study were extremely consistent with those of previous reports in the literature, further validating the reliability of the research results.…”
Section: B Asupporting
confidence: 91%
“…The ROC curves of different ultrasomics models based on eight machine-learning algorithms for predicting PNET. volume of PNET was notably smaller than that of pancreatic adenocarcinomas (25). In summary, the characteristics of the clinical and EUS ultrasonic features observed in this study were extremely consistent with those of previous reports in the literature, further validating the reliability of the research results.…”
Section: B Asupporting
confidence: 91%
“…[14] PDACs typically arise from the MPD, whereas PNETs derive from the pancreatic parenchyma. [15] . MPD dilatation is correlated to both PDACs and PNETs but more likely associated with PDACs.…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive correlation and highly significant probability between pancreatic duct dilatation and FNB result, Therefore, after the exclusion of associated pancreatic duct stones, in the CT patients with undetected small sized masses that had prominent/dilated pancreatic duct this is a good clue of raise the suspicious of underlying mass/lesion. Cai et al, (26) said that dilatation of the pancreatic duct is a warning indication for pancreatic cancers; nonetheless, tiny lumps or masses at the pancreatic tail or uncinate process might not have an impact on the pancreatic duct size. Also, Francis (27) agreed with us, as he reported that the indirect signs such as 'upstream' pancreatic duct dilation or the 'double duct' sign due to pancreatic and common bile duct obstruction are helpful in diagnosing the small iso attenuating tumors.…”
Section: Discussionmentioning
confidence: 99%